Polarization-Sensitive Second Harmonic Generation Microscopy for Investigations of Diseased Collagenous Tissues - Cisek, Richard; Joseph, Ariana; Harvey, MacAulay; Tokarz, Danielle (Frontiers in Physics, 2021)
The advancement of non-invasive quantitative optical diagnosis techniques such as polarization-sensitive second harmonic generation microscopy (PSHG) for diseases such as cancer presents opportunities for improving disease understanding and survival rates. Here, novel and developing techniques in PSHG microscopy applied for the differentiation of cancerous or diseased tissues are presented, including circular dichroism, modulation of laser linear polarization, detection of outgoing linear laser polarization, and double-Stokes Mueller. Typically, initial cancer diagnosis is performed by visual inspection of stained biopsy or surgical resection tissue sections under bright-field microscopy, however, early diagnosis is challenging due to variability in morphological interpretation of the tissues, and because cancer initiation regions can be small and easy to miss. Therefore, pathologists could benefit in identifying cancer on biopsy or surgical resection sections by using unbiased quantitative automated technologies with high spatial resolution and improved disease specificity that can check the entire slide pixel-by-pixel. Second harmonic generation microscopy offers the opportunity to measure ultrastructural alterations in collagenous scaffolds of organ tissues virtually background free on submicron-sized tissue regions. The approach is particularly interesting for cancer diagnosis applications, because during cancer initiation and progression, the collagen in the affected tissue extracellular matrix is often deregulated and becomes disorganized. This mini-review contains a thorough summary of PSHG techniques that have interrogated diseased tissues, and discusses their technical variations and successes in disease discrimination.